Highlighting Verbal Abuse of Tourists through Pragmatic Analysis: A Case Study of a South Korean YouTuber in Bunaken, Indonesia - Rahmawati Rahmawati; Andi Muh. Ruum Sya’baan; Fina Amalia Masri; Arman Arman (ELITE: Journal of English Language and Literature, 2025)
This study aims to analyze the phenomenon of verbal harassment against female tourists using a pragmatic analysis approach. The focus of this study is the interaction between a South Korean YouTuber, Jiah, and two local men in Bunaken, North Sulawesi. This study uses speech theory (Austin & Searle), speech implicature (Grice), and politeness in language (Brown & Levinson) to examine how everyday speech can encode the implicit meaning of harassment. The research method used is qualitative descriptive with pragmatic discourse analysis techniques. Data was obtained from Jiah's video transcript entitled "Become a Friend with the Om | To Bunaken from Manado". The results showed that male speakers used directive and interrogative forms of speech to control conversations and suppress opponents. Violation of the maxim of relevance and manner of giving rise to harassing implications, accompanied by violation of the principle of linguistic politeness. This phenomenon reveals power imbalances and gender bias in cross-cultural interactions. This study confirms that language serves a social function as a tool of symbolic domination, and opens up a new discussion space regarding the ethics of public communication in the tourism sector.